Improving financial education to the poor at the bottom-of pyramid: The role of social finance vis a vis financial institutions - Arsyianti, Laily Dwi; Kassim, Salina (Universiti Sultan Agung, Semarang, 2016)
This paper aims to explore the role of Islamic social ﬁnance and ﬁnancial institutions in contributing towards improving ﬁnancial inclusion through ﬁnancial education among the poor. While there have been a lot of efforts undertaken by ﬁnancial institutions, especially microﬁnance institutions, to achieve the ﬁnancial inclusion agenda, the ﬁnancial inclusion programs would normally require high operational costs which many ﬁnancial institutions would consider them as not commercially viable. The costs then are transferred back to the customers, resulting in the ﬁnancing/ credit cost higher than commercial ﬁnancial institutions. As a result, incidences of bankruptcyincrease when the cost of credit is higher. Thus, ﬁnancial education is essential for average family in managing their day to day ﬁnancial resources. While ﬁnancial institutions keep busy with ﬁnancial inclusion agenda and trying to ﬁnd the best way without disturbing their core business agenda, Islam offers social ﬁnance institution (amil and nadzir) as the solution to this problem.